The zebrafish candyfloss mutant implicates extracellular matrix adhesion failure in laminin alpha2-deficient congenital muscular dystrophy - Hall, Thomas E; Bryson-Richardson, Robert J; Berger, Silke; Jacoby, Arie S; Cole, Nicholas J; Hollway, Georgina E; Berger, Joachim; Currie, Peter D (Proceedings of the National Academy of Sciences - PNAS, 2007)
Mutations in the human laminin alpha2 (LAMA2) gene result in the most common form of congenital muscular dystrophy (MDC1A). There are currently three models for the molecular basis of cellular pathology in MDC1A: (i) lack of LAMA2 leads to sarcolemmal weakness and failure, followed by cellular necrosis, as is the case in Duchenne muscular dystrophy (DMD); (ii) loss of LAMA2-mediated signaling during the development and maintenance of muscle tissue results in myoblast proliferation and fusion defects; (iii) loss of LAMA2 from the basement membrane of the Schwann cells surrounding the peripheral nerves results in a lack of motor stimulation, leading to effective denervation atrophy. Here we show that the degenerative muscle phenotype in the zebrafish dystrophic mutant, candyfloss (caf) results from mutations in the laminin alpha2 (lama2) gene. In vivo time-lapse analysis of mechanically loaded fibers and membrane permeability assays suggest that, unlike DMD, fiber detachment is not initially associated with sarcolemmal rupture. Early muscle formation and myoblast fusion are normal, indicating that any deficiency in early Lama2 signaling does not lead to muscle pathology. In addition, innervation by the primary motor neurons is unaffected, and fiber detachment stems from muscle contraction, demonstrating that muscle atrophy through lack of motor neuron activity does not contribute to pathology in this system. Using these and other analyses, we present a model of lama2 function where fiber detachment external to the sarcolemma is mechanically induced, and retracted fibers with uncompromised membranes undergo subsequent apoptosis.